PEMBERDAYAAN KELUARGA UNTUK MENCEGAH STUNTING MELALUI EDUKASI GIZI DAN KESEHATAN DI KALURAHAN GIRIKERTO, KAPANEWON TURI, KABUPATEN SLEMAN - Retno Hendariningrum; Kartika Ayu Ardhanariswari Ardhanariswari; Sri Dwi Ari Ambarwati; Dyah Sugandini (Dharma: Jurnal Pengabdian Masyarakat, 2026)
This Community Service Program focused on empowering families to prevent stunting through nutrition and health education in Kalurahan Girikerto (village-level administration), Kapanewon Turi (sub-district), Sleman Regency, Yogyakarta, Indonesia. Stunting remains a national public health concern influenced by multiple factors, including parenting practices, nutritional quality, sanitation, and access to health services. The program applied a participatory approach that positioned families—particularly pregnant women and parents of young children—as key agents of behavioral change to promote healthy growth and optimal child development. The interventions included evidence-based nutrition education, training in the preparation of nutritious foods using locally sourced ingredients, mentoring families to adopt healthy parenting practices, and collaboration with local Posyandu cadres, health workers, and government authorities. The program also utilized interactive educational media, such as leaflets, modules, and short videos, to reinforce knowledge and daily practices. The program’s outcomes showed improved family knowledge on nutrition and parenting, behavioral changes in child feeding practices, and stronger community networks that support stunting prevention. The synergy among families, academics, and local government was crucial for program success, contributing to the national stunting reduction agenda and advancing the achievement of the Sustainable Development Goals (SDGs), particularly in health and community well-being. Keywords: stunting, health, education, nutrition, family empowerment